Imperatorin induces autophagy and G0/G1 phase arrest via PTEN-PI3K-AKT-mTOR/p21 signaling pathway in human osteosarcoma cells in vitro and in vivo - Minchao Lv; Qingxin Xu; Bei Zhang; Zhiqiang Yang; Jun Xie; Jinku Guo; Feixiong He; Wei Wang (Cancer Cell International, 2021)
Abstract Background Osteosarcoma is the third most common cancer in adolescence and the first common primary malignant tumor of bone. The long-term prognosis of osteosarcoma still remains unsatisfactory in the past decades. Therefore, development of novel therapeutic agents which are effective to osteosarcoma and are safe to normal tissue simultaneously is quite essential and urgent. Methods Firstly, MTT assay, cell colony formation assay, cell migration and invasion assays were conducted to evaluate the inhibitory effects of imperatorin towards human osteosarcoma cells. RNA-sequence assay and bioinformatic analysis were then performed to filtrate and assume the potential imperatorin-induced cell death route and signaling pathway. Moreover, quantitative real-time PCR assay, western blot assay and rescue experiments were conducted to confirm the assumptions of bioinformatic analysis. Finally, a subcutaneous tumor-transplanted nude mouse model was established and applied to evaluate the internal effect of imperatorin on osteosarcoma by HE and immunohistochemistry staining. Results Imperatorin triggered time-dependent and dose-dependent inhibition of tumor growth mainly by inducing autophagy promotion and G0/G1 phase arrest in vitro and in vivo. Besides, imperatorin treatment elevated the expression level of PTEN and p21, down-regulated the phosphorylation of AKT and mTOR. In contrast, the inhibition of PTEN using Bpv (HOpic), a potential and selective inhibitor of PTEN, concurrently rescued imperatorin-induced autophagy promotion, cell cycle arrest and inactivation of PTEN-PI3K-AKT-mTOR/p21 pathway. Conclusions This work firstly revealed that imperatorin induced autophagy and cell cycle arrest through PTEN-PI3K-AKT-mTOR/p21 signaling pathway by targeting and up-regulating PTEN in human osteosarcoma cells. Hence, imperatorin is a desirable candidate for clinical treatments of osteosarcoma.